Immunization Stress-Related Response (ISSR) from Covid-19 Vaccination First-Dose among Medical Clerkship Students in dr. Soebandi Hospital Jember - Supangat Supangat; Elly Nurus Sakinah; Achmad Ilham Tohari; Muhammad Rijal Fahrudin Hidayat; Muhammad Yuda Nugraha; Tegar Syaiful Qodar; Bagus Wahyu Mulyono (Faculty of Medicine, University of Jember, 2023)
Vaccination is one of the recommended way to eradicate Covid-19 pandemic. Unfortunately, there are still many people who refuse to get vaccinated. One of the causes is anxiety about the side effects that occur after vaccination. With this misinformation about vaccines, public anxiety is getting higher, so that more and more people are hesitant to get vaccinated. The purpose of this study was to determine the level of anxiety related to vaccines in medical students who have more knowledge about vaccines than the general public society. The anxiety assessment method used was the Hamilton Rating Scale for Anxiety (HARS) questionnaire. There were 108 medical clerkship students in this study, consisting of 25 male respondents and 83 female respondents, aged between 21-27 years. Based on the HARS-score obtained, it showed that all respondents were in the low or minimal anxiety range. Aspects of anxiety predominately appeared in the pre-vaccination phase. The differences between men and women were influenced by hormonal fluctuations and conditions before vaccination, such as stress, workload, knowledge capacity, and information obtained related to vaccination. Keywords: Anxiety, Covid-19, HARS-score, ISRR, Vaccines